Identifying the Potential of Continuity in Cash Waqf Contribution: A Descriptive Analysis - Fuadah Johari; Muhammad Ridhwan Ab. Aziz; Zurina Kefeli@ Zulkefli; Nursilah Ahmad; Mohammad Haji Alias; Kalsom Abd Wahab; Fauzi Abu Hussin; Patmawati Haji Ibrahim (Universiti Sains Islam Malaysia, 2024)
The awareness on cash waqf and the willingness to endow are imperative for the sustainability of the awqaf mechanism. In fact, waqf institutions have taken serious effort to promote waqf financing instrument in order to enhance the awareness and participation of the society. The awareness and the willingness to endow towards cash waqf in Malaysia is still lagging behind compared to other countries like Indonesia and Middle Eastern countries. Thus, in understanding the background of cash waqf endowers, this paper presents the demography and socio-economic profiles of frequent cash waqf cash waqf endower. Survey questionnaire have been distributed to 400 respondents using random sampling and 345 are valid. The data were analyzed using descriptive statistics. The findings of this study show that 55 percent of the respondents had an intention to endow cash waqf continuity is more common among married males of 36 to 40 years old. And live in rural area. Meanwhile, the socio-economic background of respondents shows that continuous cash waqf endowers were mostly graduate professionals and management workers who received formal Islamic education in university and earned between RM 1501-RM3000 monthly. These findings provide some insights of the potential continuous cash waqf endower's profile which might be beneficial to waqf agencies in accumulating waqf contribution in Malaysia.